Drowned Angels and Watery Graves: Representations of Female Suicide in Victorian Art - Cerqueira, Tânia (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
The theme of the fallen woman finding salvation in death was a popular topic in Victorian art and literature, especially during the mid-Victorian era. From the fiction of Thomas Hardy and Charles Dickens to realistic paintings, the myth of the fallen woman had a strong presence. In this article, I will focus on artistic representations of the fallen woman, such as John Everett Millais’s Ophelia and Augustus Egg’s Past and Present triptych and discuss the importance of Williams Shakespeare’s Ophelia and Thomas Hood’s poem “The Bridge of Sighs” for the conception of this mythical figure. I will also argue that, despite these artists’ efforts to mercifully portray the fallen women, in the end, they reinforced a Victorian patriarchal discourse, which regarded women as physically and intellectually weaker than men, while mythologizing this transgressing figure, created in order to remind all women of the fate they could expect if they defied the idealized conception of femininity imposed by society.